Performance criteria of dust collectors for palm oil mill boilers - Kock, J.D. (Malaysian Palm Oil Board (MPOB), 2015)
Dust collectors, installed to reduce dust emissions to within acceptable emmision standards are like any other equipment requiring regular maintenance, servicing, evaluation and testing to verify and ensure efficient/optimal operation. In some cases, the air pollutants are hardly visible. For this reason, a faulty dust collector is only identified by implication, sometimes long after the deterioration has taken place, exposing the environment to harmful pollutants. Even properly designed systems, from reputable suppliers, may show decrease in performance characteristics due to wear, poor maintenance and changing process conditions. Apart from this, many dust collectors are installed without proper design and qualtiy control procedures and many simply copied from original suppliers. Some of these systems are inadequate from the beginning. Evaluation of mechanical dust collectors, installed after oil palm mill boilers are most important for ensuring that they are operating according to the design specifications. Dust collectors are often installed without verifying the performance during commissioning with only stack emission measurements carried out. As the dust concentration from the boiler may vary, stack emission measurements do not show the performance of the dust collector system. Only simultaneous iso-kinetic measurements at the inlet and outlet of the dust collector make it possible to determine the actual dust collection performance characteristic of the system installed. This performance characteristic as measured can be used for verifying the design specifications. After the performance characteristic has been determined, future measurements will show if any deterioration has taken place. These measurements should be part of the maintenance programme of the mill. This will not only assist in ensuring that the emission complies with the set standards but also in planning maintenance work on dust collector in advance.